Modeling and Designing of Active Vibration Isolation Platform - Mikhailov, Valery; Kopylov, Alexey; Kazakov, Alexander (Journal of Robotics and Control (JRC), 2024)
The most important task of ensuring the quality of operation of technological and research equipment is its effective protection from external vibration effects in the area of low frequencies, at which resonance phenomena are manifested. For this purpose, various types of vibration isolation systems are used, which are divided into passive and active. Passive systems effectively suppress vibrations at frequencies above 40-50 Hz, at lower frequencies such systems are ineffective as they cannot compensate for resonance phenomena. In this case, active vibration isolation systems are used. The active dampers and platform based on magnetorheological (MR) elastomers presented in the paper demonstrated higher vibration isolation efficiency in the frequency range of 0.3-3 Hz compared to the piezoelectric system and in the frequency range of 0.3-20 Hz compared to the platform based on electromagnetic power drive. At these frequencies, the vibration displacement amplitude transfer coefficient was less than 0.075.  The use of MR effect makes it possible to regulate the stiffness and deformation of the elastic active element made of MR elastomer by changing the magnitude of magnetic induction. In this case it is possible to control dynamic and precision characteristics of the active damper, as well as to increase the efficiency of vibration isolation.  During dynamic modelling of the active MP damper the differential equations and transfer functions of its elements were determined. Modelling in Simulink MATLAB software environment allowed to determine the transient process of damper movement under the influence of harmonic oscillations, select the type of regulator and calculate its tuning parameters. Experimental studies were carried out on a vibration test bench and confirmed the modelling results at frequencies of 0.3-50 Hz. At frequencies higher than 50 Hz passive vibration isolation begins to prevail due to absorption of vibration energy in the MR elastomer, which is not taken into account in the modelling. The experimental amplitude-frequency response of the platform showed high vibration isolation efficiency at frequencies of 0.3-100 Hz with vibration displacement amplitude transfer coefficient less than 0.075.